Avaliação in silico do potencial antimicrobiano dos constituintes químicos de óleos essenciais de plantas do gênero Lippia a partir da essencioteca do professor Francisco de Abreu Matos - Soares, Igor Lima (2023)
Francisco José de Abreu Matos was a researcher renowned for his research on medicinal plants, especially species from the Northeast of Brazil. During his career, he conducted several phytochemical investigations, leaving a unique documental collection containing hundreds of analyses of essential oils that make up the "Essencioteca de Matos". However, the pharmacochemical potential of most of these plant derivatives has not been fully elucidated. Given the emergence of resistant strains of microorganisms, there is a need to promote the bioprospecting of antimicrobial natural products. Computational simulations concatenated with phytochemical study techniques can optimize the discovery of new drugs from natural products. The objective of this study was to evaluate the antimicrobial pharmacochemical potential of volatile constituents of Northeastern plant species present in the "Essencioteca de Matos" belonging to the genus Lippia, seeking to contribute to the discovery of new phytochemicals. This work was structured in two main steps. The first step was a documental study of the Essencioteca records, including cataloguing, typing and digitalization, botanical nomenclature review and multivariate statistical analysis of phytochemical data of the species by Principal Component Analysis (PCA) and Hierarchical Cluster Analysis (HCA). The second step refers to in silico analyses for the prediction of biological properties as well as pharmacokinetic and toxicological parameters. 900 essential oil analysis sheets were found, of this total, 95 sheets from the genus Lippia were included for evaluation covering the species L. thymoides, L. origanoides, L. alba, L. microphylla, L. grata and L. alnifolia. Chemometric analyses by PCA and HCA allowed establishing several plant chemotypes for the species. The in silico analyses enabled the prediction of several biological properties for the volatile constituents of the species, considering a spectrum of antibacterial, antifungal and antiviral actions. Beta-farnesene showed the highest potential biological action (Pa=0.781) against rhinoviruses and inhibiting action of squalene epoxidase (Pa=0.213) and high potential as antifungal (Pa=0.607), and despite being poorly absorbed by the intestine according to BOILED-Egg and Caco-2 models, was the phytoconstituent with the best skin permeability and was not shown to be mutagenic in Ames test simulations, making it promising as a lead molecule and/or prototype for the synthesis of analogues as antifungal drug candidates. The Essencioteca of the Professor Francisco José de Abreu Matos can be considered a valuable source of information about aromatic plants from the Northeast of Brazil.